Effect of brain GYM exercises on balance in preschool children: a randomized controlled trail - Samar Taher Elbasuony Elbanna; Hebatallah Mohamed Kamal; Emad Abdul Maksoud Mahgoub; Shorouk Elshennawy (Journal of the Pakistan Medical Association, 2023)
Objectives: To investigate the effect of Brain Gym exercise on preschool children’s balance achievement. Method: The randomised controlled trial was conducted at EL-Moasis kindergarten from May to September 2021 and comprised preschool children of either gender aged 4-6 years who were randomised into intervention group A which received Brain Gym exercise for 15-30 minutes per day, three times a week, for eight consecutive weeks, and control group B which received the usual kindergarten activities. Balance was assessed by One Leg Standing Test and Functional Reach Test. Data was analysed using SPSS 20. Results: Of the 30 subjects, 15(50%) were in each of the 2 groups. There were 13(43.3%) boys and 17(56.7%) girls with overall mean age 4.99±0.67 years. However, the study completed had 27(90%) subjects. Overall, there were 26(%) right-handed subjects. Post-intervention, there was significant intra-group improvements (p<0.05), but there were no significant inter-group differences (p>0.05). Conclusion: No significant benefits were seen in the balance of preschool children exposed to Brain Gym exercise. RCT registration: The RCT was registered retrospectively at The Pan African Clinical Trials Registry (PACTR) (Trial #: PACTR202208886771106 Date of Approval: 15/08/2022). Link: https://pactr.samrc.ac.za/Search.aspx Keywords: Leg, Exercise, Brain, Gym